2002
DOI: 10.1046/j.1471-8286.2002.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific TaqMan probes for simultaneous identification of (Gadus morhua L.), haddock (Melanogrammus aeglefinus L.) and whiting (Merlangius merlangus L.).

Abstract: We report the development of a multiplex, single tube (TaqMan) PCR assay for the identification of three commercially important gadoid species, the cod (Gadus morhua L.), the haddock (Melanogrammus aeglefinus L.) and the whiting (Merlangius merlangus L.). The assay unambiguously identifies known adult tissue samples, and ethanol‐preserved eggs from all three species with greater than 98% accuracy, providing a powerful tool for the development of catch independent stock assessment methods, mapping of spawning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 3 publications
0
84
0
Order By: Relevance
“…In this approach, either a taxon-specific DNA-probe is developed (e.g. Taylor et al 2002) or cloning or pyro-sequencing are used to evaluate the presence of a broader range of taxa using DNA sequences (e.g. Cytochrome Oxidase I [COI] barcodes).…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, either a taxon-specific DNA-probe is developed (e.g. Taylor et al 2002) or cloning or pyro-sequencing are used to evaluate the presence of a broader range of taxa using DNA sequences (e.g. Cytochrome Oxidase I [COI] barcodes).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 5S rDNA is highly repeated in the genome and the NTS is quite short, the PCR amplification of a small amount of DNA is extremely robust, particularly if compared with single copy genes. mtDNA markers are commonly employed for species identification [9,12,13]. As most of the mtDNA genome is coding, between species differentiation is often based on single nucleotide polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…After reading relevant information about demersal fish stock declines [Ref. 4 and others] and the utility of molecular markers for stock assessment [3,9], a final discussion may be carried out concerning the application of molecular techniques in fisheries management. A final additional 2-h session could be convenient for this purpose.…”
Section: ) and Af335598 (M Merluccius)mentioning
confidence: 99%
“…The method was also used in heat and vacuum treated foodstuffs, however, without quantification (Hird et al, 2005). Taylor et al (2002) identified three commercially significant gadoid species (Gadus morhua, Melanogrammus aeglefinus and Merlangius merlangus) using the multiplex (TaqMan) PCR method based on variation in a 103-bp region of the ATP synthase subunit six (ATPase6) and eight (ATPase8) genes.…”
Section: Real-time Pcrmentioning
confidence: 99%